Debromination of 2, 2′, 4, 4′-tetrabromodiphenyl ether (BDE-47) by synthetic Pd/Fe0 and Cu/Fe0 in different protic solvents. (December 2018) - Li, Huafeng; Wang, Jin; Wang, Rui; Huang, Kaibo; Luo, Wanying; Tao, Xueqin; Dang, Zhi; Yin, Hua; Guo, Chuling; Lu, Guining
Abstract: Polybrominated diphenyl ethers (PBDEs) belong to a class of persistent organic pollutants (POPs), with potential toxicity to the liver, reproductive system, and development of mammals. The highly toxic and concentrated congener, 2, 2′, 4, 4′-tetrabromodiphenyl ether (BDE-47), was chosen to investigate debromination mechanisms by the two synthetic iron-based bimetals (Pd/Fe 0 and Cu/Fe 0 ) in two protic solvents (water and ethanol). SEM, XPS, and BET analyses showed that the synthetic bimetals Pd/Fe 0 and Cu/Fe 0 were spherical with diameters of about 100 nm and loaded with ∼1% (wt%) of Pd and Cu, respectively. GC-MS was used for the analysis of degradation products and the chromatograms showed that both Pd/Fe 0 and Cu/Fe 0 bimetals had effective reducing properties in water solvent. In ethanol solvent, debromination of BDE-47 by Pd/Fe 0 showed a similar high activity, but BDE-47 could be hardly degraded by Cu/Fe 0 . The dominant debromination products of BDE-47 by Pd/Fe 0 and Cu/Fe 0 were ortho -substituted and para -substituted BDEs, respectively. Active H-atomic transfer was found to play a key role in the debromination of BDE-47 by Pd/Fe 0 in both, water and ethanol, with a preference for para -debromination along with the formation of dibenzo-p-furan (DF) as the by-product, mainly in water. In contrast, electron transfer with a preference for ortho -debromination was found to play a predominant role for Cu/Fe 0 system in water. More importance should be provided to active H-atomic transfer for its high efficiency. In-depth study on the mechanism of formation of by-product DF would be significant for its higher toxicity, possibility of accumulation and migration in the environment. Highlights: Nanoscale bimetals Pd/Fe 0 and Cu/Fe 0 were simplistically synthesized successfully. Major mechanism between active H-atomic transfer and electron transfer were further proved. para -Br and ortho -Br was preferentially debrominated for active H-atomic transfer and electron transfer, respectively. DF mainly produced with active H-atomic transfer in solvents rich in active H-atomic.